Análise de instrumentos de avaliação motora de crianças com base na perspectiva da teoria de resposta ao item - Nazario, Patrik Felipe (2016)
Research in motor development field has been focusing on the search of factors that lead children to an atypical development throughout the life span. However, it is only possible to verify the children's motor development through motor evaluation's tools. Herewith, this thesis aims to verify the suitability of motor tasks, through discrimination and difficult parameters of each task, of motor assessment tools Movement Assessment Battery for Children 2th Edition (MABC-2), Test of Gross Motor Development 2th Edition (TGMD-2) and Körperkoordinations Test für Kinder (KTK). 582 children have participated in the first and second study, of both sexes, aged 3 to 5 years. For the TGMD-2, 159 children of both sexes, aged 7 to 8 years, were evaluated, in the third study. In the fourth study, 345 children of both sexes, aged 5 to 14 years have participated. All children were evaluated in only a single tool. Data were analyzed from reliability analysis, exploratory and confirmatory factor analysis; and, task's parameters analysis (difficulty and discrimination) through two-parameter logistic model from item response theory - TRI. Overall results showed that the motor task of MABC-2, TGMD-2 and KTK have not equivalent suitability in evaluating the motor performance of the children which have participated of this thesis. The motor task drawing trail has not suited in the model adjusted for the children and was withdrawal from the subsequent analysis. In the TGMD-2 tool, several criteria used to assess motor skills do not showed adequate levels of difficulty and discrimination capacity, which means that those criteria have low quality of information and are not useful in the evaluation of motor performance, for those children evaluated in this study. Results from KTK showed that the motor tasks have no equivalence in the degree of difficulty. Finally, it is possible to conclude that the evaluation of motor performance, for the children that have participated of this study, from MABC-2, TGMD-2 and KTK, may not seem adequate if not taken into account the peculiarities each motor task features, such as the degree of difficulty and discrimination capability of the task has in each motor skill level found in the group of children.